Comparison of Guided Exercise and Self-Paced Exercise After Lumbar Spine Surgery: A Randomized Controlled Trial - Seong Son; Han Byeol Park; Kyeong Sik Kong; Byung Rhae Yoo; Woo Kyung Kim; Jae Ang Sim (Life)
Background: The efficacy of postoperative exercise rehabilitation after spine surgery is controversial, and a protocol for exercise treatment and detailed outcomes based on functional activity have not yet been established. This study aimed to determine the efficacy of exercise rehabilitation after lumbar spine surgery. Methods: A prospective, randomized controlled trial was conducted in 40 patients who underwent lumbar spine surgery (20 patients each in the exercise and control groups) for 12 weeks. Clinical outcomes were assessed using the visual analog scale (VAS) for pain and EuroQol-5 Dimensions 5-Level version (EQ-5D-5L). Body proportions, including body mass index, total muscle mass, and body fat percentage were analyzed. Functional activity was evaluated based on the range of motion of the lumbar spine, strength and endurance of lumbar flexion/extension, flexibility, 6 min walking test, single-leg stance, coordination, and gait pattern analysis. Results: The exercise group showed significantly greater improvement in VAS for pain (66.67% versus 20.00%, p < 0.001) and EQ-5D-5L (45.56% versus 20.00, p = 0.039) compared to the control group. Serial assessment revealed significant improvement in strength of lumbar flexion/extension, 6 min walking test, single-leg stance, coordination, and gait patterns in the exercise group compared to the control group. In particular, the single-leg stance time for the affected leg improved more markedly in the exercise group (280.9% versus 48.7%, p < 0.001). Conclusion: Tailored postoperative exercise after lumbar spine surgery is effective in reducing pain and enhancing functional recovery, including strength and balance.